Should organs at risk (OARs) be prioritized over target volume coverage in stereotactic ablative radiotherapy (SABR) for oligometastases? a secondary analysis of the population-based phase II SABR-5 trial. (May 2023) - Eufemon Cereno, Reno; Mou, Benjamin; Baker, Sarah; Chng, Nick; Arbour, Gregory; Bergman, Alanah; Liu, Mitchell; Schellenberg, Devin; Matthews, Quinn; Huang, Vicky; Mestrovic, Ante; Hyde, Derek; et al.
Highlights: In oligometastatic SABR, under-coverage of the planning target volume (PTV) to prioritize organs-at-risk (OAR) constraints has been common practice. In this secondary analysis of the large, population-based, phase II SABR-5 trial, under-coverage of the PTV, as represented by the coverage compromise index (CCI), did not predict for worse local recurrence (LR) and progression-free survival (PFS) rates. This study highlights the importance of prioritizing OARs during SABR planning in order to achieve the recently reported low toxicity rates of the SABR-5 trial. Abstract: Background and Purpose: Stereotactic ablative radiotherapy (SABR) for oligometastases may improve survival, however concerns about safety remain. To mitigate risk of toxicity, target coverage was sacrificed to prioritize organs-at-risk (OARs) during SABR planning in the population-based SABR-5 trial. This study evaluated the effect of this practice on dosimetry, local recurrence (LR), and progression-free survival (PFS). Methods: This single-arm phase II trial included patients with up to 5 oligometastases between November 2016 and July 2020. The protocol-specified planning objective was to cover 95 % of the planning target volume (PTV) with 100 % of the prescribed dose, however PTV coverage was reduced as needed to meet OAR constraints. This trade-off was measured using the coverage compromise index (CCI), computed as minimum dose received by the hottest 99 % of the PTV (D99) divided by the prescription dose. Under-coverage was defined as CCI < 0.90. The potential association between CCI and outcomes was evaluated. Results: 549 lesions from 381 patients were assessed. Mean CCI was 0.88 (95 % confidence interval [CI], 0.86–0.89), and 196 (36 %) lesions were under-covered. The highest mean CCI (0.95; 95 %CI, 0.93–0.97) was in non-spine bone lesions (n = 116), while the lowest mean CCI (0.71; 95 % CI, 0.69–0.73) was in spine lesions (n = 104). On multivariable analysis, under-coverage did not predict for worse LR (HR 0.48, p = 0.37) or PFS (HR 1.24, p = 0.38). Largest lesion diameter, colorectal and 'other' (non-prostate, breast, or lung) primary predicted for worse LR. Largest lesion diameter, synchronous tumor treatment, short disease free interval, state of oligoprogression, initiation or change in systemic treatment, and a high PTV Dmax were significantly associated with PFS. Conclusion: PTV under-coverage was not associated with worse LR or PFS in this large, population-based phase II trial. Combined with low toxicity rates, this study supports the practice of prioritizing OAR constraints during oligometastatic SABR planning.